EFL Students' Experiences With Anxiety In Learning English Speaking: A Narrative Inquiry - Arrahmani, Novi Ida Fitriyah; Ekowijayanto, Mochlis (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Speaking anxiety in English as a Foreign Language (EFL) learning can significantly impact students' academic performance. This study explores EFL students’ experiences with different types of speaking anxiety and the strategies they use to manage it. Using a qualitative descriptive approach through narrative inquiry, data were collected from two students at SMA Nurul Jadid, selected through purposive sampling. Thematic analysis was conducted following the Miles and Huberman model. The study identified six key themes: anxiety due to lack of experience and knowledge, anxiety during live evaluations, context-based anxiety (online vs. offline), anxiety under limited preparation, shifting perspectives on anxiety, and coping strategies. Common strategies included seeking support from trusted individuals and intensive practice. The level of anxiety varied among individuals, with distinctions between general and situational anxiety. The findings support the Foreign Language Anxiety framework by Horwitz, Horwitz, and Cope, particularly the components of communication apprehension, test anxiety, and fear of negative evaluation. However, a new insight emerged: participants reported lower anxiety in online settings compared to offline ones, suggesting that anxiety is influenced by environmental factors, not solely by personality traits. This highlights the dynamic nature of speaking anxiety in EFL contexts.